PDTM-12. DLX2 TRANSCRIPTIONAL REGULATION OF CENTRAL NERVOUS SYSTEM CELL FATE RELEVANCE TO PEDIATRIC DIFFUSE MIDLINE GLIOMAS WITH HISTONE 3 MUTATIONS. (5th November 2018) - Nevin, Mikaela; Song, Xiaohua; Becher, Oren; Underhill, D Alan; Godbout, Roseline; Eisenstat, David
Abstract: INTRODUCTION: Diffuse intrinsic pontine glioma (DIPG) is refractory to current therapy with less than 2% long term survivors. The identification of histone H3.1/H3.3 K27M mutations in most DIPG has provided new insights into the biology of this fatal disease. The DLX homeobox genes are expressed in the developing forebrain. The Dlx1/Dlx2 double knockout (DKO) mouse loses tangential GABAergic interneuron migration to the neocortex. We have identified genes that encode glutamic acid decarboxylase (GAD) enzymes as direct transcriptional targets of DLX1/DLX2. In DIPG patients with H3.3 K27M mutations there is decreased Dlx2 and increased expression of the myelin transcription factor, Myt1 . There is loss of H3 K27 tri-methylation (me 3 ) expression in many tumors with K27M mutations. METHODS AND RESULTS: We used bioinformatics approaches and chromatin immunoprecipitation (ChIP) assays to identify Olig2, Nkx2.2 and Myt1 promoter sequences as candidate DLX2 targets in vivo . DNA binding specificity was confirmed by gel shift assays in vitro . The functional consequences of Dlx2 co-expression with reporter constructs of ChIP-isolated promoter fragments of Olig2 and Nkx2.2 demonstrated repression of gene targets in vitro . qPCR showed increased Olig2 and Nkx2.2 expression in the DKO forebrain. Stable transfection of Dlx2 into a murine DIPG (mDIPG) cell line with the K27M mutation resulted in increased expression of Gad1 and Gad2 and decreased expression of Olig2 and Nkx2.2 . Dlx2 stable transfection also resulted in decreased migration, invasion and colony number and size in vitro . Of significance, we demonstrated decreased expression of H3.3 K27M and restoration of H3.3 K27me 3 expression in Dlx2 stable transfected mDIPG cells. CONCLUSIONS: DLX transcription factors promote GABAergic interneuron and concomitant inhibition of oligodendroglial differentiation in neural progenitors by repression of a suite of genes including Olig2 and Nkx2.2 . Restoration of H3 K27me 3 expression in DIPG provides a promising lead towards exploration of differentiation as a therapeutic strategy for DIPG.